CRITICAL PEDAGOGY(IES) FOR ELT IN INDONESIA - Kasey R. Larson (TEFLIN, 2014)
Â This paper will explore the theoretical underpinnings that present a rationale for the use of critical pedagogy as an English Language Teaching (ELT) approach in Indonesia. A brief description of critical pedagogy is given, followed by a detailed rationale for its use including an overview of critical pedagogy studies done in Asia, an exploration of the curriculum and teaching approach decreed by the Indonesian Ministry of Education and Culture, and calls for critical pedagogy by Indonesian scholars and teachers. This paper will conclude with some beginning steps that can be undertaken by teachers who want to implement a more critical approach to teaching.Â